A linear logic approach to the composition of RESTful web services. (2015) - Zhao, Xia; Liu, Enjie; Yu, Hong Qing; Clapworthy, Gordon J.
RESTful web services, which are declarative, lightweight and easy to access, are already widely used for exposing services on the internet and have attracted increasing interest from industry. The rising number of services being implemented and made available on the web is creating a demand for modelling techniques that can abstract REST design from the implementation in order to better specify, analyse and implement large-scale RESTful web systems. It can also help by providing suitable RESTful web service composition methods which can reduce costs by efficiently re-using the large number of services that are already available and by exploiting existing services for complex business purposes. This paper introduces a formal model of RESTful web services in linear logic and proposes a formal method approach for RESTful web service composition based on planning using linear logic via theorem proving. This is a two-stage planning method that finds resources for the composition at both the abstract resource and the service operation levels. It greatly improves the searching efficiency and guarantees the correctness and completeness of the service composition process. The paper demonstrates a further validation of the planning method through its implementation in the interactive Coq logic proof assistant.